The Impact of Workload and Job Satisfaction on Employee Intention to Leave in the Logistics Industry: A Study of Small and Medium Enterprises (SMEs) in Selangor, Malaysia - Teh, Zhi Yuan; Yusoff, Mohd Zarir (Research in Management of Technology and Business, 2025)
Small and medium-sized firms (SMEs) are critical to the logistics industry, enabling efficient transportation of products and services. Employees in these SMEs play crucial roles in various areas, including transportation and supply chain management. However, SMEs have a significant turnover of employees due to challenges such as managing workloads and job satisfaction. High workloads in logistics SMEs cause stress and burnout, which reduces job satisfaction and increases turnover rates. Employees quit due to low job satisfaction, which is impacted by management, the work environment, and work-life balance. This study examines the relationship between workload, job satisfaction, and employee turnover in logistics SMEs in Selangor, Malaysia. The purpose is to give insights for SMEs to manage workloads better and improve employment satisfaction, resulting in lower turnover rates and increased organisational stability and growth. Utilising a quantitative approach, data were collected from 225 employees through structured questionnaires. Multiple regression analysis revealed that workload positively correlates with turnover intention, while job satisfaction shows a negative relationship. These findings highlight the importance of managing workload and enhancing job satisfaction to reduce employee turnover in the logistics sector. This research offers practical insights for SMEs to improve retention strategies and foster a more supportive work environment.